2017
DOI: 10.1016/j.saa.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrochemical dual channel sensing of Cu2+ using functionalized furo[2,3-d]pyrimidines-2,4[1H,3H]-diones

Abstract: Owing to their easy accessibility and high degree of structural and functional diversity, many multicomponent reactions (MCRs) have been a rich source of conjugate π-systems, functionalised chromophores (or fluorophore) and redox active molecules. Despite their high explorative potential and practical benefits, only a few MCR products have been so far investigated for their metal sensing abilities. In the present report, two furopyrimidinones (FPys) based molecular systems have been synthesized by [4+1] cycloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The performance of these sensors was evaluated in comparison to previously reported Cu 2+ and GSH sensors, particularly in terms of K a and LOD values. The results presented in Table demonstrate that the sensors developed in this study offer comparable performance to those reported in the literature, making them promising candidates for copper and glutathione sensing applications. ,, …”
Section: Resultssupporting
confidence: 64%
“…The performance of these sensors was evaluated in comparison to previously reported Cu 2+ and GSH sensors, particularly in terms of K a and LOD values. The results presented in Table demonstrate that the sensors developed in this study offer comparable performance to those reported in the literature, making them promising candidates for copper and glutathione sensing applications. ,, …”
Section: Resultssupporting
confidence: 64%
“…The adversities associated with metal cations warrant the need for chemical sensors that can easily and selectively detect the cations at low concentrations. A number of mechanistically different sensors are already available to detect different metal ions (Jeong and Yoon, 2012;Kumar et al, 2017). A fluoresceinbased chemosensor has been reported to detect Cu +2 ions in aqueous solutions in nanomolar concentrations (Jun et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another chemosensor but for the detection of Cu(II) ions are furo [2,3-d]pyrimidines-2,4[1H,3H]-diones 85. The chromophores consist of fused furopyrimidine and are generated via multicomponent strategy with a chromophore approach (Supplementary Material S29) (Kumar et al, 2017). The MW assisted three-component reaction of 1,3-dimethylbarbituric acid, benzaldehyde and respective isocyanides corresponding isocyanides proceeds via Knoevenagel condensation, [4 + 1] cycloaddition, and a 1,3-H shift to form two furopyrimidinones in excellent yields.…”
Section: Nitrogen Heterocyclesmentioning
confidence: 99%